PENGARUH PEMBERIAN BERAS MERAH TERHADAP KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELLITUS TIPE 2 DI RSUD DR. SADIKIN KOTA PARIAMAN - Wilda Laila; Tika Dwita Adfar; Dwi Syaputri Yanti; Hendra Mukhlis; Efri Yeni (Ensiklopedia of Journal, 2026)
Diabetes Mellitus Type 2 is a non-communicable disease characterized by an uncontrolled increase in blood glucose levels. The prevalence of diabetes mellitus continues to increase in Indonesia. One effort to control blood glucose levels is to eat foods with a low glycemic index, rich in fiber and antioxidants. One of these ingredients is brown rice. The purpose of the study was to determine the effect of giving brown rice to blood glucose levels in patients with type 2 diabetes mellitus at the dr Sadikin Regional General Hospital, Pariaman City. The type of research is Pre Experiment with one group pretest and posttest design. The number of samples is 15 people with Accidental Sampling sampling technique. Blood glucose levels were checked before and after being given brown rice for 8 days. Data were analyzed by Wilcoxon's test. It was found that the blood glucose level before being given brown rice was 356.1 mg/dl and after being given brown rice 165.6 mg/dl and it was found that there was an effect of giving brown rice on the blood glucose levels of patients with type 2 diabetes mellitus. This study concludes that brown rice has an effect on reducing blood glucose levels in patients with type 2 diabetes mellitus. It is recommended for people with type 2 diabetes mellitus to consume brown rice as a substitute for white rice to control their blood glucose levels, and carry out further research with other factors and comparison groups.Keywords: Diabetes Mellitus, Brown Rice, Blood Glucose Levels